THE INFLUENCE OF SELF-EFFICACY, SELF-ACTUALIZATION, AND LEARNING ENVIRONMENT ON ACHIEVEMENT MOTIVES OF CLASS XII STUDENTS OF SMA ADHYAKSA I KOTA JAMBI - Tiara Ayu Lestari; Ali Idrus; Sofyan Sofyan (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This study aims to analyse the effect of self-efficacy, self-actualisation, and the learning environment both individually and collectively on achievement motives in class XII students at SMA Adhyaksa 1 Jambi. This research is classified as research with the type of expost-facto using a quantitative approach. The population in this study were all XII grade students at Adhyaksa 1 Jambi High School totalling 134 people, and the sampling technique used was total sampling. The data collection technique in this study used a questionnaire instrument. The data obtained were analysed using descriptive statistical methods using simple regression and multiple regression techniques. The results of this study prove that self-efficacy has a significant effect on student achievement motives with a magnitude of influence of 49.1%. Self-actualisation variables have a significant effect on student achievement motives with a large influence of 49.9%. The learning environment variable has a significant effect on the motive for achievement in students with a magnitude of influence given of 34.2%. The results of multiple regression analysis prove that together the variables of self-efficacy, self-actualisation and learning environment have a significant effect on students' achievement motives with a value of the influence given of 60.4%.